Looking at the State University’s Organizational Culture Through the Lens of Part-Time Faculty - Abe, Lorlyn T.; Anselmo, Charlie T.; Ingente , Ma. Andrea G. (Future Science / FSH-PH Publications, 2025)
This study investigated the organizational culture of a state university in the Philippines through the perceptions of part-time faculty members using the Organizational Culture Assessment Instrument (OCAI). The OCAI assesses six dimensions of organizational culture: dominant characteristics, organizational leadership, employee management, organizational glue, strategic emphasis, and success criteria. Ten contract-of-service faculty members participated in the study, allocating 100 points among four cultural types (Clan, Adhocracy, Market, and Hierarchy) for each dimension to represent the existing and preferred cultures. The results showed that the existing culture was dominated by Clan culture (31.17 points), characterized by a friendly work environment and high employee commitment, followed by Hierarchy (27.83 points), Adhocracy (21.67 points), and Market cultures (19.33 points). The preferred culture profile indicated a desire for slight shifts, with increases in Adhocracy (2.66 points) and Market (5.17 points) cultures, and decreases in Clan (0.84 points) and Hierarchy (7 points) cultures. The differences between the existing and preferred profiles were less than 10 points, suggesting that there was no urgent need for cultural change. The findings contribute to understanding the organizational dynamics in Philippine state universities and may inform institutional policies and practices that support part-time faculty engagement and effectiveness. Recommendations include implementing strategies to balance the desired cultural shifts while maintaining the strengths of the existing clan culture, providing professional development opportunities, and conducting further research to examine the impact of organizational culture on faculty outcomes.